Análise do ensino-aprendizagem de alunos do ensino médio usando a sequência didática “Os passeios aleatórios do Homem de Ferro” - Campos, Guilherme Augusto Silvestre de (2024)
In this work, through the McNemar Test and the proficiency test, we show the student's level of learning through a didactic sequence based on “Mônica's Random Walks” which for us was adapted to “Iron Man's Random Walks” with students from high school at a public school in the city of Sorocaba. The proposal for the didactic sequence was developed based on the theoretical foundation of didactic engineering, in which the working steps during the process were divided into theoretical and practical experiments, where students had to answer two nine-question questionnaires before and after the didactic sequence, which were tabulated and analyzed using the McNemar test. The test brought us a measurement of the student's learning, which could be, does not apply or applies, but it leaves a certain doubt, as it did not consider low variations, for this reason we created a percentage proficiency test so that it was possible a visualization by segments and thus have more data and information to carry out the necessary comparisons. Therefore, we would be able to measure through the comparisons proposed by both the McNemar test and the proficiency test how much the student was or was not able to learn the pre-established concepts in this proposal.